Prenatal diagnosis of 5p deletion syndrome in a female fetus leading to identification of the same diagnosis in her mother. (6th August 2014) - Nguyen, Joanne Macayran; Gamble, Candace; Smith, Janice L.; Raia, Marianna; Johnson, Anthony; Czerwinski, Jennifer
<x xml:space="preserve">Abstract</x> What's already known about this topic? Elevated or decreased human chorionic gonadotrophin from second trimester maternal serum screens have been seen in pregnancies affected with 5p deletion syndrome (5p−syndrome). Clinical variability does exist for 5p−syndrome, although the more severe, classic presentation is best described with limited descriptions available for milder presentations. What does this study add? Analyte values were normal in this case that suggests that normal fetal anatomy and maternal serum analytes may be present in the second trimester of pregnancy in cases of 5p−syndrome. It is important to further define the mild end of the 5p−phenotypic spectrum that may allow increased recognition of previously undiagnosed, affected individuals.